2012
DOI: 10.1016/j.reprotox.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide and insect repellent mixture (permethrin and DEET) induces epigenetic transgenerational inheritance of disease and sperm epimutations

Abstract: Environmental compounds are known to promote epigenetic transgenerational inheritance of disease. The current study was designed to determine if a “pesticide mixture” (pesticide permethrin and insect repellent N,N-Diethyl-meta-toluamide, DEET) promotes epigenetic transgenerational inheritance of disease and associated DNA methylation epimutations in sperm. Gestating F0 generation female rats were exposed during fetal gonadal sex determination and the incidence of disease evaluated in F1 and F3 generations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(156 citation statements)
references
References 60 publications
2
153
0
1
Order By: Relevance
“…There was no increase in ovarian disease in direct fetal exposed F1 or germline exposed F2 generation vinclozolin or DDT lineage rats compared to controls [30,31]. Therefore, as previously observed with most exposures, negligible ovarian disease is present following direct exposure [25,2729], with the exception of BPA and phthalates [26]. This indicates that there was an epigenetic transgenerational increase in susceptibility to ovarian disease in rats ancestrally exposed to DDT or vinclozolin (Figure 1).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…There was no increase in ovarian disease in direct fetal exposed F1 or germline exposed F2 generation vinclozolin or DDT lineage rats compared to controls [30,31]. Therefore, as previously observed with most exposures, negligible ovarian disease is present following direct exposure [25,2729], with the exception of BPA and phthalates [26]. This indicates that there was an epigenetic transgenerational increase in susceptibility to ovarian disease in rats ancestrally exposed to DDT or vinclozolin (Figure 1).…”
Section: Resultsmentioning
confidence: 71%
“…There was a significant increase in ovarian disease in transgenerational F3 generation DDT and vinclozolin lineage rats at one year of age compared to F3 generation controls (Figure 1). Previous studies have shown that transgenerational increases in ovarian disease were detected following exposures to plastic derived compounds bisphenol A (BPA) and phthalates (DBT & DEHP) [26], dioxin (TCCD) [25], pesticides permethrin and DEET [27], jet fuel hydrocarbons [28], and methoxychlor [29], with nearly 100% disease frequency. Therefore, the transgenerational inheritance of increased ovarian disease can occur after exposure to a variety of environmental toxicants.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a series of studies have shown that exposing the gestating mammalian female F0 to environmental factors during embryonic gonadal sex determination causes changes in DNA methylation that are retained in adult F1–3 male progeny, which produce sperm with altered DNA methylation (812). The inherited changes were monitored in the third generation after treatment (1315).…”
Section: Introductionmentioning
confidence: 99%
“…Shorter adult height, less schooling, reduced economic productivity, lower offspring birth weight, high glucose concentrations, high blood pressure, and harmful lipid profiles were more prevalent among those exposed to prenatal malnutrition. [57] This is a good example of how malnutrition without necessarily widespread famine as that of the Dutch (1944Dutch ( -1945, Chinese (1959Chinese ( -1961, or the Biafran (1967)(1968)(1969)(1970), could influence offsprings' adult Rat Maternal exposure to permethrin and DEET (pesticide and insect repellent mixture) during pregnancy [288] Increased pubertal abnormalities, testis disease, and ovarian disease (primordial follicle loss and polycystic ovarian disease) in F3 generation…”
Section: Hypomethylation Of the Pancreatic Il13ra2 Genementioning
confidence: 99%
“…[280][281][282][283][284] Other commonly available environmental and air pollutants including pesticides, agricultural chemicals, and others have also been shown to induce extensive epigenetic changes that are inherited transgenerationally with consequent increases in the risk of adult NCCDs. [285][286][287][288][289][290][291][292] From the beginning of the industrial revolution, humans have undoubtedly been exposed to a wide range of chemicals and environmental pollutants that could have programed the risk of many diseases in different communities. Moreover, at the beginning of the industrial revolution no legislations were available to control the industrial production of many pollutants or the use of chemicals to manufacture materials for domestic use as we have today.…”
Section: Smoking Alcohol Pollutants and Other Environmental Chemicalsmentioning
confidence: 99%